Impact of ambulance off-load delays on mortality in patients with chest pain. (3rd October 2022) - Dawson, L; Andrew, E; Stephenson, M; Nehme, Z; Bloom, J; Cox, S; Anderson, D; Lefkovits, J; Taylor, A J; Kaye, D; Smith, K; Stub, D
Abstract: Background: Ambulance off-load delays in transferring patient care to emergency departments (EDs) are increasingly common, but it is unclear whether clinical outcomes are impacted. Methods: Population-based cohort study of ambulance attendances for non-traumatic chest pain transported to ED in Victoria, Australia (1/1/2015–30/6/2019) excluding patients transported to hospital with "lights and sirens" or triaged as ED category 1. Multivariable models were used to assess the relationship between ambulance off-load times and 30-day mortality and ambulance re-attendance for chest pain. Results: The study included 213, 544 ambulance attendances for chest pain (mean age 62 [SD 18] years; 51% female). Median ambulance off-load times increased across the study period from 21 minutes (interquartile range [IQR] 15–30) in 2015 to 24 minutes (IQR 17–37) in 2019. Patients were divided into tertiles according to off-load times with 69, 247 patients included in tertile 1 (0–17 minutes), 73, 109 patients in tertile 2 (18–28 minutes), and 71, 188 patients in tertile 3 (>28 minutes). In multivariable models, ambulance off-load delays were associated with higher unadjusted and adjusted rates of 30-day mortality (1.57% tertile 3 vs. 1.29% tertile 1, adjusted risk difference 0.28% [95% CI 0.16% - 0.42%], p<0.001) and ambulance re-attendance for chest pain (9.89% tertile 3 vs. 8.59% tertile 1, adjusted risk difference 1.30% [95% CI 1.00% - 1.61%], p<0.001). Similarly, in analysis using off-load times as a continuous variable with restricted cubic splines, a non-linear increase in adjusted odds ratio for mortality was observed (Figure 1). Conclusions: Delays in ambulance off-load times appear to be associated with increased mortality and ambulance re-attendance risk among chest pain cohorts. This study has important policy implications given the increasing frequency of off-load delays in many healthcare settings. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Alfred health